PENGARUH KONSENTRASI TEPUNG PEPAYA DAN LAMA PENYIMPANAN TERHADAP KETAHANAN L. acidophilus FNCC 0051 TERIMOBIL PADA KONDISI ASAM LAMBUNG DAN GARAM EMPEDU - Sucipto, Mariska; Widyastuti, Theresia Endang Widoeri; Kuswardhani, Indah (Jurnal Teknologi Pangan dan Gizi, 2016)
Papaya powder added as a prebiotic, but its concentration and storage time in UHT milk as a carrier can impact on viability of immobilized cell in gastric acid and bile salt condition. The purpose of this study was to determine the effect of the interaction of papaya powder concentration and storage time and also the influence of each these factors on the survival of immobilized L. acidophilus FNCC 0051 in gastric acid and bile salt. The research design used a Randomized Block Design (RBD) of factorial design. Papaya powder concentrations as the first factor consisting of two levels (3% b/v and 6% b/v) and the storage times as the second factor consisting of five levels (0, 7, 14, 21, and 28 days). Each treatment combinations repeated three times. Data were analyzed by ANOVA (Analysis of Variance) at Î± = 5%. Based on the results, use of 6% concentration papaya powder significantly increasing the survival of immobilized L. acidophilus FNCC 0051 on condition of gastric acid. Meanwhile, interaction of papaya powder concentration and storage time significantly affect the resistance of immobilized L. acidophilus FNCC 0051 on bile salt condition. Storage along 14 days decreasing the cells number, but the survival cell on bile salt condition increased by the use of 6% concentration of papaya powder during 21 days of storage. The highest survival with decreased cell 0,1459 log cfu/g obtained from combination of 6% concentration of papaya powder at 21 days of storage time.